Perspective taking in the human brain: complementary evidence from neuroimaging studies with media-based naturalistic stimuli and artificial controlled paradigms - Jääskeläinen, Iiro P.; Kosonogov, Vladimir (Frontiers in Human Neuroscience, 2023)
Perception and interpretation of various types of events and information in life crucially depend on one’s perspective. A specific perspective can be explicitly adopted, for example, via instructing an experimental subject, implicitly via a priori information given to subjects, and by subjects’ personality traits or cultural background. The neural basis of perspective taking has been addressed in a number of recent neuroimaging studies, some of which have used movies and narratives as media-based stimuli to pursue a holistic understanding of the phenomenon under ecologically valid conditions. Results across these studies suggest that the human brain flexibly adapts to support the information-processing needs of different perspectives, however, also that inferior temporal-occipital areas and posterior-medial parietal areas are engaged across different perspectives. These findings are complemented by studies that have investigated specific aspects of perspective taking with highly controlled experimental designs. They have disclosed involvement of the temporoparietal junction in visual perspective taking and the importance of the affective component of the pain matrix when empathizing with others’ pain. Identification with the protagonists also seems to matter, as dorsomedial vs. ventromedial prefrontal areas are recruited when the protagonist is dissimilar vs. similar to self. Finally, as a translational aspect, perspective taking can, under certain conditions, serve as an effective emotion regulation technique, wherein lateral and medial regions of the prefrontal cortex seem to support reappraisal processes. Together, findings from studies with media-based stimuli and more traditional paradigms complement each other to gain a comprehensive understanding of the neural basis of perspective taking.